First person – Katja Graf and Antonia Last (Disease Models & Mechanisms, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Katja Graf and Antonia Last are co-first authors on ‘ Keeping Candida commensal: how lactobacilli antagonize pathogenicity of Candida albicans in an in vitro gut model’, published in DMM. Katja is a postdoc and Antonia is a PhD student in the lab of Bernhard Hube at the Hans Knöll Institute (HKI) investigating molecular pathogenicity mechanisms.